Servant Leadership of School Administrators, Organizational Support and Teachers’ Creative Self-Efficacy Affecting Innovative Work Behavior of Teachers under the Rayong Primary Educational Service Area Office 1 - Pummarin, On-in; Phutiariyawat, Jantarat (Dhammathas Academic Journal, 2026)
This research aimed to: 1) examine the levels of servant leadership of school administrators, organizational support, teachers’ creative self-efficacy, and innovative work behavior; 2) investigate the relationships among these variables; and 3) identify the predictive factors influencing teachers’ innovative work behavior under the Rayong Primary Educational Service Area Office 1. The predictor variables included servant leadership of school administrators, organizational support, and teachers’ creative self-efficacy. This study employed a quantitative research design. The sample consisted of teachers working in schools under the Rayong Primary Educational Service Area Office 1 during the 2025 academic year. The research instrument was a five-point rating scale questionnaire with item-objective congruence (IOC) indices ranging from 0.60 to 1.00 and an overall Cronbach’s alpha coefficient of 0.980. The data were analyzed using frequency, percentage, mean, standard deviation, Pearson’s product-moment correlation coefficient, and stepwise multiple regression analysis. The findings revealed that: 1. Servant leadership of school administrators, organizational support, teachers’ creative self-efficacy, and teachers’ innovative work behavior were overall at a high level. 2. All variables were positively correlated at a high level, with statistical significance at the .01 level (r = 0.741–0.784). 3. Servant leadership of school administrators, organizational support, and teachers’ creative self-efficacy jointly predicted teachers’ innovative work behavior at 74.90 percent, with statistical significance at the .001 level. The findings suggest that school administrators should promote servant leadership alongside strengthening organizational support systems and enhancing teachers’ creative self-efficacy in order to foster innovative work behavior in educational settings more effectively.